Effects of virtual rehabilitation on postural control of individuals with Parkinson disease - Bacha,Jéssica Maria Ribeiro (2021)
ABSTRACT Parkinson's disease causes a progressive decline of motor and cognitive functions, often affecting postural control. Training through virtual reality has been shown to be effective in improving this condition. This study aims to analyse the effects of the Kinect Adventures! games in postural control of people with Parkinson's disease. Ten individuals diagnosed with idiopathic Parkinson's disease, in stages I to III of the Hoehn & Yahr scale, aged between 48 and 73 years, were selected. Fourteen training sessions of one hour each, twice a week, were performed. Individuals were evaluated pre, post-intervention and 30 days after the last session of intervention by a force platform that measured the oscillation area and velocity of the centre of pressure in ten different sensory conditions and the Limits of Stability. Limits of Stability showed a statistically significant increase immediately after the training the 14 sessions, as were observed and there were no significant changes in oscillation area and velocity immediately after the intervention or 30 days after the end of training. The results of this study indicate that the training with Kinect Adventures! Games improve the postural control of people with Parkinson's disease, by increasing the Limits of Stability.